IMPLEMENTASI FINANSIAL LITERASI DAN FINANSIAL TEKNOLOGI DALAM PENGELOLAAN KEUANGAN UMKM DI KABUPATEN KOLAKA - Fitri Kumalasari Fitri; Agus Zul Bay; Fetni; Perduti Lestari Rulimo (Halu Oleo University, 2024)
The current condition of micro, small, and medium enterprises is not as bad as it used to be. However, in this developmental process, micro, small, and medium enterprise managers face various challenges, including limited financial understanding and a lack of skills in applying technology for financial management. This study employs qualitative methods to understand the implementation of Financial Literacy and Financial Technology in managing micro, small, and medium enterprises' finances in Kolaka Regency using purposive sampling techniques. Qualitative descriptive data analysis techniques were used. According to Bogdan in Hardan et al. (2020), data analysis is a systematic process of collecting and describing information from various sources such as interviews, field notes, and other materials. The aim of this process is to facilitate a better understanding and communicate the results to others. Research shows that financial literacy and financial technology in managing MSME finances in Kolaka Regency are working well, helping MSMEs manage financial resources effectively and utilize digital payments to increase access to financial services and financial inclusion.